Revitalisasi Model Pengembangan Kurikulum Fakultas Ekonomi dan Bisnis Islam Berbasis Standar KKNI dan Islamic Entrepreneurship - Sugeng Riyadi; Badaruddin Badaruddin (El-Jizya: Jurnal Ekonomi Islam, 2018)
Curriculum is an important variable in education. To measure the success of education, standardization becomes one of important strategies in strata-ization of the alumni of a specific educational institution, in this case, Islamic Economics and Business Faculty. The policy transformation of Indonesian National Qualification Framework as inevitability of standardization group covers all higher educations including Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. In this context, the mastery of knowledge and entrepreneurship practice that is inherent with the concept of Islamic theory (Islamic Entrepreneurship) is one of the primary indicators.